2023
DOI: 10.1167/tvst.12.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multiple Machine Learning Models for Predicting Number of Anti-VEGF Injections in the Comparison of AMD Treatment Trials (CATT)

Abstract: Purpose To apply machine learning models for predicting the number of pro re nata (PRN) injections of antivascular endothelial growth factor (anti-VEGF) for neovascular age-related macular degeneration (nAMD) in two years in the Comparison of AMD (age-related macular degeneration) Treatments Trials. Methods The data from 493 eligible participants randomized to PRN treatment of ranibizumab or bevacizumab were used for training (n = 393) machine learning models including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…There has been an advance in recent research in AMD utilizing machine learning algorithms, regarding not only diagnosing or classifying diseases but also predicting A OCT demonstrates the first recurrence at 1.1499 months (within three months) after the loading phase, predicting a value higher than 0.5 with a prediction of 0.6391, which is true positive. B OCT demonstrates the first recurrence at 7.3595 months (after three months) after the loading phase, predicting a value lower than 0.5 with a prediction of 0.1362, which is true negative [32], and Romo-Bucheli et al revealed AUC of 0.85 in detecting the patients with low and high treatment requirement in nAMD [33]. Meanwhile, machine learning algorithms that predict visual acuity after anti-VEGF therapy may also encourage patients to adhere to intravitreal therapy and contribute to personalized medicine.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an advance in recent research in AMD utilizing machine learning algorithms, regarding not only diagnosing or classifying diseases but also predicting A OCT demonstrates the first recurrence at 1.1499 months (within three months) after the loading phase, predicting a value higher than 0.5 with a prediction of 0.6391, which is true positive. B OCT demonstrates the first recurrence at 7.3595 months (after three months) after the loading phase, predicting a value lower than 0.5 with a prediction of 0.1362, which is true negative [32], and Romo-Bucheli et al revealed AUC of 0.85 in detecting the patients with low and high treatment requirement in nAMD [33]. Meanwhile, machine learning algorithms that predict visual acuity after anti-VEGF therapy may also encourage patients to adhere to intravitreal therapy and contribute to personalized medicine.…”
Section: Discussionmentioning
confidence: 99%